2013
DOI: 10.1542/hpeds.2012-0053
|View full text |Cite
|
Sign up to set email alerts
|

A Pediatric Residency Experience With Surgical Co-management

Abstract: A surgical co-management model in pediatric residency training presented important opportunities for development of residents' knowledge and skills in perioperative care and interprofessional teamwork.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Both groups recognize the importance of collaboration as surgical team members Factors underlying to communication (independence, interdependence, self-concern, awareness of others, conflict style) - Kirschbaum, Rask, Brennan, Phelan, and Fortner (2012) 37 USA Pre- and posttest survey (n = 44) Communication Obstetrics / Anesthesiology Determine effectiveness of multidisciplinary team training on organizational culture and team communication Nonsignificnat variance between obstetricians and anesthesiologists. Significant variance from pretest and posttest suggesting the training used in the study can improve communication for more effective collaboration Factors underlying to communication (independence, interdependence, self-concern, awareness of others, conflict style) - Orchard, King, Khalili, and Bezzina (2012) 38 Canada Tool development based on literature review Collaboration Not specified Develop, test, and refine the assessment of interprofessional team collaboration scale - Discrete elements of interprofessional care (partnership, shared decision making, cooperation, coordination) - Carr et al (2013) 7 USA Rotation evaluation / Program leadership meetings / Survey (n =26) Co-management Pediatrics / Surgery Describe a 5-year experience with a co-management model in a pediatric residency program The dyadic model of transition led to positive changes in self-assessed preparedness to provide transition care and engage colleagues around the care of shared patients - Increased knowledge and trust between pediatric residents and surgeons Nayak, Beaulieu, Rubin, Jafi, & Lipson (2013) 39 USA Survey (n = 160) Communication Radiology Identify referring physicians’ preferences about radiology reports and quantify perceived value of multimedia reports compared with narrative text reports Radiology reports with embedded images are viewed favorably with potential for beneficial outcomes...…”
Section: Resultsmentioning
confidence: 99%
“…Both groups recognize the importance of collaboration as surgical team members Factors underlying to communication (independence, interdependence, self-concern, awareness of others, conflict style) - Kirschbaum, Rask, Brennan, Phelan, and Fortner (2012) 37 USA Pre- and posttest survey (n = 44) Communication Obstetrics / Anesthesiology Determine effectiveness of multidisciplinary team training on organizational culture and team communication Nonsignificnat variance between obstetricians and anesthesiologists. Significant variance from pretest and posttest suggesting the training used in the study can improve communication for more effective collaboration Factors underlying to communication (independence, interdependence, self-concern, awareness of others, conflict style) - Orchard, King, Khalili, and Bezzina (2012) 38 Canada Tool development based on literature review Collaboration Not specified Develop, test, and refine the assessment of interprofessional team collaboration scale - Discrete elements of interprofessional care (partnership, shared decision making, cooperation, coordination) - Carr et al (2013) 7 USA Rotation evaluation / Program leadership meetings / Survey (n =26) Co-management Pediatrics / Surgery Describe a 5-year experience with a co-management model in a pediatric residency program The dyadic model of transition led to positive changes in self-assessed preparedness to provide transition care and engage colleagues around the care of shared patients - Increased knowledge and trust between pediatric residents and surgeons Nayak, Beaulieu, Rubin, Jafi, & Lipson (2013) 39 USA Survey (n = 160) Communication Radiology Identify referring physicians’ preferences about radiology reports and quantify perceived value of multimedia reports compared with narrative text reports Radiology reports with embedded images are viewed favorably with potential for beneficial outcomes...…”
Section: Resultsmentioning
confidence: 99%
“…Further, there is much less information available on pain management in this select patient cohort. Notably, pain control and management was ranked first (followed by fluid and electrolytes, respiratory care, and nutrition management) in a survey asking pediatric residents which areas they felt the co-management of patients helped them learn most [10].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a randomized trial involving comanaged orthopedic patients showed a decrease in complication rates [8], while a similar system between neurosurgeons and hospitalists at a teaching hospital resulted in increased perceived quality of care and decreased costs (by $1500 per visit) [9]. In another study focusing on a surgical co-management model implemented in pediatric residency program, one of the primary outcomes reported was gains in knowledge and skills by residents in pain management [10].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, multiple models of hospitalist involvement in perioperative care have evolved across the United States. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] To consolidate knowledge and experience and to develop a framework for providing the best care for surgical patients, the Society of Hospital Medicine organized the Perioperative Care Work Group in 2015. This framework was designed for interdisciplinary collaboration in building and strengthening perioperative care programs.…”
Section: Conclusion: Thementioning
confidence: 99%